Significance of Jalaluddin Roman's Scientific Heritage in Improving Social Intelligence in Modern Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the importance of Jalaluddin Rumi’s scientific heritage in regulating the system of social relations between individuals and society from a scientific and theoretical point of view.